The Implementation of Waste Management in Bandung Green and Clean Program Based on Multistakeholder - A Hadian Pratama Hamzah; Sohifah Sohifah; Nurhasanah Nurhasanah (Universitas Batanghari, 2022)
The Program of BGC is a community empowerment program to manage the environment in particular self-governing waste treatment management in the level of Bandung City (Kota Bandung). This Program city is built by the partnership of Unilever Indonesia Foundation, Bandung Environmental management Agency, Pikiran Rakyat Daily Newspaper, Rase FM Radio, and Institute for Appropriate Technology Implementation and Bandung Family Welfare Development. This study has objective to determine how the achievement of BGC program implementation (in particular waste management program) considered of aspects of relevance, effectiveness, efficiency, impact, and sustainability included the factors that influence the achievement of success/failure of the BGC programs implementation which is related to waste management considered of the aspects of the problem characteristic, program characteristics and environmental variables. The method used in this study are dominant qualitative and less dominant quantitative combined with descriptive analysis method. Results of this study has shown that the implementation of Bandung Green Clean programs related to waste management in Bandung has been relevant to the needs and conditions of Bandung people. However, the implementation of programs related to waste management Bandung Green and Clean has not succeeded in achieving the goal namely change people's behavior in waste management. Most of activities such as waste sorting, composting and recycling inorganic waste have to be done at the community level. Therefore the amount of waste volume of neighborhood Association-citizens Association Bandung Green and Clean participant has decreased only reached 10% of the target achievement of the waste management program by 95% The failure of this program, caused by characteristic factors of the problems encountered in BGC programs related to waste management with the target group coverage program that is too large and too heterogeneous as well as the scope of behavior change, therefore it has an effect on easy or not the waste management programs implemented in the field, which in turn also affect to the objectives of the Bandung Green and Clean program achievement related to waste management policy.